Recommendations for green development of motor biofuel industry in China: A review - Zhang, Zongxi; Li, Gang; Zhang, Yinghua; Zhang, Jiang; Song, Chuanzeng; Zhou, Yuguang (International Journal of Agricultural and Biological Engineering, 2020)
Motor biofuel is one kind of clean and sustainable fuel extracted from living organisms or obtained by the transformation of organisms, which can be used to replace fossil fuels. Nowadays, motor biofuel is an important direction for the development and utilization of renewable energy. More attention has been given to the development and promotion of motor biofuel and relative technologies all over the world. This research introduced the history of motor biofuel, the classification of motor biofuel as well as the strategies and policies made domestically and internationally in order to promote the development of motor biofuel, and also pointed out some of the urgent problems faced during the development of motor biofuels and put forward some suggestions for the future development of motor biofuel in China. Keywords: green development, motor biofuel, biodiesel, bioethanol, emission, renewable energy replacement DOI: 10.25165/j.ijabe.20201305.3862 Citation: Zhang Z X, Li G, Zhang Y H, Zhang J, Song C Z, Zhou Y G. Recommendations for green development of motor biofuel industry in China: A review. Int J Agric & Biol Eng, 2020; 13(5): 218–225.